Ethnicity and Racism in Cyprus National Pride and Prejudice? - Stevens, Peter A. J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Investigating the relationship between ethnic pride and prejudice in the divided community of Cyprus, this book focuses on the ethnic stereotypes that Greek and Turkish Cypriot secondary school students develop of each other and other ethnic groups in Cyprus.
Keywords: Social sciences; Sociology; Social structure; Social inequality; Cultural studies; Ethnicity; Emigration and immigration; Social Sciences; Migration; Ethnicity Studies; Sociology, general; Cultural Studies; Social Structure, Social Inequality; Sociology of Family, Youth and Aging; Electronic books